EVALUASI BIAYA DAN WAKTU PADA PROYEK PENGGANTIAN JEMBATAN DENGAN MENGGUNAKAN METODE KONSEP NILAI HASIL - Adityawan Sigit (TEKNISIA, 2019)
On the implementation of project, there could have been problem in performance of time and cost that caused project that had been completed not to go according to plan. Therefore, performance evaluation is needed so that project can be carried out as planned and can also evaluate of project performance. In this research, time and cost performance will be evaluate using the earned value concept method in the Project for Replacement of the Nanga Tepuai-Nanga Semangut Section Bridge. Earned Value Concept can provide information about  progress position of project time and cost performance in a certain period of time. The stages of this research begin with data collection of S-Curves, RAB, Weekly Progress Report and Financial Report. Next, determine three indicators, that is BCWS, BCWP and ACWP, which is then used to analyze the Schedule Variance, Schedule Performance Index, Cost Variance, Cost Performance Index, Estimation at Schedule, and Estimation at Completion. The result of this research showed, from time performance, in month-1 until month-6, value of SV is postitive and the value of  SPI is more than 1, which means that the project is implemented faster than plan, and in month-7 the value of SV is 0 and the value of SPI is 1, which means that the project is implemented according to the plan. About cost performance, in month-1 the value of CV is negative and the value of CPI is less than 1, which means the costs incurred for implementating more than the plan, and in month-2 until month-7 the value CV is positive and the value of CPI is more than 1, which means the costs incurred for implementating less than the plan. The best EAS value is obtained in reporting month-2, it’s 3,63 months. The best EAC value is obtained in reporting month-4, it’s Rp. 7.239.951.844,01.